Acute kidney injury in critically ill COVID-19 patients in a tertiary hospital: short and long-term kidney and patient outcomes - Juliana Alves Manhães de Andrade; Gisele Meinerz; Raphael Palma; Eduardo Rech; Marco Antônio Vinciprova Dall’Agnese; Cristiane Bundchen; Fernanda Bordignon Nunes; Gisele Branchini; Elizete Keitel (Brazilian Journal of Nephrology)
Abstract Introduction: Acute kidney injury (AKI) in the setting of COVID-19 is associated with worse clinical and renal outcomes, with limited long-term data. Aim: To evaluate critically ill COVID-19 patients with AKI that required nephrologist consultation (NC-AKI) in a tertiary hospital. Methods: Prospective single-center cohort of critically ill COVID-19 adult patients with NC-AKI from May 1st, 2020, to April 30th, 2021. Kidney replacement therapy (KRT), recovery of kidney function, and death at 90-day and 1-year follow-up were evaluated. Results: 360 patients were included, 60.6% were male, median age was 66.0 (57.0–72.0) years, 38.1% had diabetes, and 68.6% had hypertension. AKI stages 1, 2, and 3 were detected in 3.6%, 5.6%, and 90.8% of patients, respectively. KRT was indicated in 90% of patients. At the 90-day follow-up, 88.1% of patients died and 10.0% had recovered kidney function. Female gender (p = 0.047), older age (p = 0.047), AKI stage 3 (p = 0.005), requirement of KRT (p < 0.0001), mechanical ventilation (p < 0.0001), and superimposed bacterial infection (p < 0.0001) were significantly associated death within 90 days. At 1 year, mortality was 89.3%. Amongst surviving patients, 72% recovered kidney function, although with significantly lower eGFR compared to baseline (85.5 ± 23.6 vs. 65.9 ± 24.8 mL/min, p = 0.003). Conclusion: Critically ill COVID-19 patients with NC-AKI presented a high frequency of AKI stage 3 and KRT requirement, with a high 90-day mortality. Surviving patients had high rates of recovery of kidney function, with a lower eGFR at one-year follow-up compared to baseline.